Evaluasi Context, Input, Process, dan Product Program Permata di Lembaga Layanan Pendidikan Tinggi Wilayah I Sumatera Utara - Armiadi Asamat; Slamet Widodo; Yoyok Hendarso (Journal of Education, Humaniora and Social Sciences (JEHSS), 2021)
This evaluation research was conducted to analyze and find out how the Permata Program was carried out in LLDikti Region I during the period 2016 to 2018. This research was conducted using a qualitative approach combined with the CIPP Evaluation Model (Context, Input, Process, and Product). The data collection consists of semi-structured interview method, literature study, and documentation. The informants of this study consisted of three elements; managers of the LLDikti’s HES Program, Managers of the HES Program at universities, and alumni of the HES Program. Informants were determined purposively, with special criteria coming from universities that were consistently active in the HES Program during the three years of its implementation. The results showed that the program has benefits for its participants and requires some improvements in its implementation. Program inhibiting factors: funding administration, control of input aspects; the availability of information of study program curriculum information, and communication between institutions. The supporting factor for implementing the Permata Program is the political will. Benefits of the Permata Program: the occurrence of scientific cultural exchanges to enrich and strengthen the uniqueness of each university; the occurrence of regional cultural exchanges to strengthen patriotism; gain student’s insight and experience; and probability of increasing the quality of study program accreditation.